Association between First Trimester Antidepressant Use and Risk of Spontaneous Abortion. Issue 9 (25th July 2019) - Wu, Pingsheng; Velez Edwards, Digna R.; Gorrindo, Phillip; Sundermann, Alexandra C.; Torstenson, Eric S.; Jones, Sarah H.; Chan, Ronna L.; Hartmann, Katherine E.
Abstract : Study Objective: The potential for maternal antidepressant use to influence the risk of spontaneous abortion, one of the most important adverse pregnancy outcomes, is not clear. We aimed to assess whether first trimester antidepressant exposure was associated with an increased risk of spontaneous abortion. Design: Community‐based prospective cohort study (Right from the Start). Setting: Eight metropolitan areas in North Carolina, Tennessee, and Texas. Participants: A total of 5451 women (18 years of age or older) who were planning to conceive or were pregnant (before 12 weeks of completed gestation) and were enrolled in the study between 2000 and 2012; of those women, 223 used antidepressants (selective serotonin reuptake inhibitors [SSRIs] only [170], SSRIs and non‐SSRIs [9], and non‐SSRIs only [44]) during their first trimester, and 5228 did not (never users). Measurements and Main Results: First trimester antidepressant use was determined during a first trimester telephone interview. Spontaneous abortion was self‐reported and verified by medical records. The association of first trimester antidepressant use and spontaneous abortion was assessed by using Cox proportional hazard regression. Among the 5451 women enrolled, 223 (4%) reported first trimester antidepressant use, and 659 (12%) experienced a spontaneous abortion. SSRIs were the most common class of antidepressants used (179 [80%]). Compared with women who never used antidepressants during the first trimester of pregnancy, women who reported antidepressant use were 34% (adjusted hazard ratio [aHR] 1.34, 95% confidence interval [CI] 0.97–1.85) more likely to experience a spontaneous abortion after adjusting for covariates. Women who reported ever using SSRIs were 45% (aHR 1.45, 95% CI 1.02–2.06) more likely to experience a spontaneous abortion compared with never users. When time of loss relative to the time of interview was taken into consideration, the association between first trimester SSRI use and spontaneous abortion was significant only among those with losses before the interview (aHR 1.49, 95% CI 1.04–2.13) but was not significant among those with losses after the interview (aHR 0.43, 95% CI 0.06–3.15). Conclusion: The association between use of first trimester antidepressants, particularly SSRI use, and spontaneous abortion was significant only among women whose exposure status was assessed after loss. In this instance, reporting bias may create a spurious association. Future studies should take the timing of data collection relative to the timing of loss into consideration.